BIOETICS AND RELIGION: FROM THE BEGINNING OF BIOETHICS TO THE GLOBAL ETHIC - Marjanović, Miloš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The founders of bioethics were American biochemist Van Rensseler Potter (1970) and the German theologian Fritz Jahr (1926). Potter conceptualized global bioethics, and Jahr formulated bioethical imperative: "Respect every living being as an end in itself and treat it. if possible, as such." American and European bioethics have been developed independently, mutually ignoring. Only recently have appeared attempts to link the global and integrative bioethics, which is a significant part relies on Jahr’s  ideas. There are discussed the relations between early secularized but still the dominant scientific and  suppressed theological bioethics in the United States, as well as between the transhumanist,  bioconservative and critical currents in bioethics. With desecularization (religious renewal) fanned the struggle between scientific and religious worldviews which is particularly intense on the field of bioethics. Religious approach does not give the epistemological and methodological contributions to bioethics, but rather refers to the moral limits of human intervention on itself and the surrounding nature. From its very beginnings, from Jahr’s  bioethical imperative to the Declaration toward a global ethic (adopted by the Parliament of the World Religions in Chicago in 1993), a respect of life as life, in all its forms and stages, is  moral constant of religious perspective in bioethics, thus it becomes and its constituent